The Role Of OCB As A Mediation Variable On Employee Performance - Muhammad Irfan Al Asyqy; Ida Aryati DPW; Sarsono (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The purpose of this study was to investigate the effect that organizational citizenship behavior (OCB) has on employee performance as a mediation factor at the General Section of the Surakarta City Regional Secretariat. The data in this study are quantitative in nature. The information that was utilized in this research derived from primary sources, specifically questionnaires that were given out to a minimum of 75 employees of the General Section of the Regional Secretariat of Surakarta City. Saturated sampling is the method that is being used for the sample. The methods of data analysis that were used included statistical analysis, including Convergent Validity, Discriminant Validity, and Composite Reliability using SmartPLS 3.0. The findings indicated that organizational culture and work ethic both directly and indirectly had a significant and positive effect on employee performance at the General Section of the Surakarta City Regional Secretariat. The findings of the study also indicate that OCB, in its role as a mediating variable, has a stronger indirect influence than a direct effect on the performance of employees in the General Section of the Regional Secretariat of Surakarta City. It is anticipated that the findings of this study will contribute positively to the discourse that leaders engage in to enhance organizational culture, work ethic, and organizational citizenship behavior for the purpose of improving employee performance.